Consumer data research - Paul A. Longley; James Cheshire; Alexander D. Singleton (UCL Press, 2018)
Big Data collected by customer-facing organisations - such as smartphone logs, store loyalty card transactions, smart travel tickets, social media posts, or smart energy meter readings - account for most of the data collected about citizens today. As a result, they are transforming the practice of social science. Consumer Big Data are distinct from conventional social science data not only in their volume, variety and velocity, but also in terms of their provenance and fitness for ever more research purposes. The contributors to this book, all from the Consumer Data Research Centre, provide a first consolidated statement of the enormous potential of consumer data research in the academic, commercial and government sectors - and a timely appraisal of the ways in which consumer data challenge scientific orthodoxies.
Keywords: 300; big data; consumer data research; consumer; consumer behaviour; Demography; Ethnic group; Smart meter; Twitter; Bevölkerungsstruktur; Datenerhebung; Kundenanalyse; Großbritannien